The Bauschinger effect in stainless steel orthodontic wires - Gullotta Antonino; West Victor C.; Hazel Roger J. (Sciendo, 1987)
The existence and clinical importance of the Bauschinger effect has received little attention in the orthodontic literature. Essentially, the Bauschinger effect describes the reduction in yield stress of a metal when the direction of defamation is reversed. A method of evaluating this phenomenon in orthodontic wires ts described and its clinical implications are discussed.